IDENTIFIKASI KOMPLEKS MAKAM KUNO ANAKIAMBU’UTOBU WEPOINDO DIKELURAHAN MELUHU KECAMATAN MELUHU KABUPATEN KONAWE PROVINSI SULAWESI TENGGARA - Abrory Dicky Fernandho; syahrun syahrun (SANGIA: Jurnal Penelitian Arkeologi, 2017)
The purpose of this study was to find out theshape of the tomb, and to find out whether thetomb is a culture of Islam or pre-Islamic times. The research method used was descriptive analysisconsisting of several stages, namely surface survey, interview, observation, reviewing documents,documentation and then added with morphological analysis. The results of this study indicate that thesite of the ancient tomb complex of anakia mbu'utobu Wepoindo in Meluhu Village, Meluhu District,Konawe Regency, Southeast Sulawesi Province is generally in the form of a square, which was laterbuilt using a mound, has tombs and tombstones. There are 4 types of tombs based on the number oftombs, namely types A1, A2, A3, A4 and A5, and there are 4 forms of headstone namely type, PS, LJ,TB and P. In addition there are loose findings in the form of a bowl with the number 6, plates with anumber of 10 glass with number 1 and total currency 1. Through the form of tombs, loose findings andtheir history, it can be concluded that the ancient tomb complex of anakia mbu'utobu Wepoindo is anIslamic tomb which later was still influenced by the megalithic tradition.